2013
DOI: 10.2224/sbp.2013.41.6.995
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender and sex-role orientation on sexual attitudes among Turkish university students

Abstract: My purpose was to investigate the effects of gender and sex-role orientation on attitudes toward autoeroticism/masturbation, abortion, pornography, homosexuality, premarital sex, and sexual coercion among Turkish university students. Participants were 468 undergraduate students from 3 large urban universities in Ankara. The Turkish version of the Bem Sex-Role Inventory (BSRI; Bem, 1974) and the Sexual Knowledge and Attitude Test for Adolescents (SKAT-A; Fullard, Johnston, & Lief, 1998) were used to collect dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…Regarding attitudes toward solitary sexual behaviors (masturbation and sexual fantasies) and use of erotic material, it has been found that women have more positive attitudes than men. These results are inconsistent with those reported in other studies where no differences in attitudes toward masturbation were found between men and women (Abramson et al, 1981;Driemeyer et al, 2017;Kelley et al, 1997;Sümer, 2013) or in those studies where men were found to have more positive attitudes towards masturbation (Sümer, 2015;Wang et al, 2007), sexual fantasies (Santos-Iglesias et al, 2013;Sierra et al, 2021), or pornography use (Traeen et al, 2004) than women.…”
Section: Limitationscontrasting
confidence: 99%
“…Regarding attitudes toward solitary sexual behaviors (masturbation and sexual fantasies) and use of erotic material, it has been found that women have more positive attitudes than men. These results are inconsistent with those reported in other studies where no differences in attitudes toward masturbation were found between men and women (Abramson et al, 1981;Driemeyer et al, 2017;Kelley et al, 1997;Sümer, 2013) or in those studies where men were found to have more positive attitudes towards masturbation (Sümer, 2015;Wang et al, 2007), sexual fantasies (Santos-Iglesias et al, 2013;Sierra et al, 2021), or pornography use (Traeen et al, 2004) than women.…”
Section: Limitationscontrasting
confidence: 99%
“…In the study of Khamsehee, women with mental imaginations and cultural stereotypes such as obedience, shyness, sensitivity to other's needs, affection, and making mutual understanding and being emotional in their sexual role framework reported more sexual dissatisfaction with sexual behaviors. [ 37 ] Meanwhile, women with a manhood role framework such as independency, self-sufficiency, defending their beliefs, daringness, leadership, and other manhood characteristics and who had combined these features with their female sexual role framework reported no sexual dissatisfaction. Therefore, sexual education results in correction of beliefs and incorrect information and helps the individuals acquire proper knowledge and attitude and improve their sexual behaviors, although in a study conducted by Norani et al ., no significant difference was observed between men and women concerning their sexual knowledge and attitude and their effect on marital satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sexual education results in correction of beliefs and incorrect information and helps the individuals acquire proper knowledge and attitude and improve their sexual behaviors, although in a study conducted by Norani et al ., no significant difference was observed between men and women concerning their sexual knowledge and attitude and their effect on marital satisfaction. [ 36 ] In the studies of Sumer,[ 37 ] Huston et al .,[ 38 ] Kilmann and Vendemia,[ 39 ] and Aiquaiz et al .,[ 40 ] a significant difference was observed between men's and women's sexual function. In these studies, the men were more easy-going concerning sexual problems, compared to women, and paid more attention to obtain pleasure.…”
Section: Discussionmentioning
confidence: 99%
“…Although many changes have occurred as part of Turkey's modernization, cultural and traditional views of sexuality seem resistant to some of these influences (Hatipoglu-Sumer, 2013). In most parts of Turkey, sexuality is not yet accepted as a natural and healthy human function (Cicek et al, 2022;Evcili and Golbasi, 2017).…”
Section: Introductionmentioning
confidence: 99%